Green food waste as an environmental resource in residential areas - Monica Michel Zacharia; Marwa Dabaieh; Nabeel Elhady (Cairo : Monica Michel Zacharia, 2018)
The world is struggling with the {u2018}Waste{u2019} crisis that has negative impact on the environment. This study aims at investigating potential solutions through recycling organic waste on site. Case study mapping with empirical methods were used for investigation.Findings were as follows: 1) a huge amount of municipal organic waste is missed during the traditional collecting process, 2) it takes a huge distance, energy and effort to reach the recycling factories or landfill, 3) compost can be produced on the rooftops. As a conclusion, residential composting can potentially reduce significant amounts of the municipal solid waste (MSW) generation in Egypt
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Architectural Engineering
Issued also as CD
Keywords: Green food waste; Recycling; Waste